Hemorrhagic Fever-Causing Arenaviruses: Lethal Pathogens and Potent Immune Suppressors - Brisse, Morgan E.; Ly, Hinh (Frontiers in Immunology, 2019)
Hemorrhagic fevers (HF) resulting from pathogenic arenaviral infections have traditionally been neglected as tropical diseases primarily affecting African and South American regions. There are currently no FDA-approved vaccines for arenaviruses, and treatments have been limited to supportive therapy and use of non-specific nucleoside analogs, such as Ribavirin. Outbreaks of arenaviral infections have been limited to certain geographic areas that are endemic but known cases of exportation of arenaviruses from endemic regions and socioeconomic challenges for local control of rodent reservoirs raise serious concerns about the potential for larger outbreaks in the future. This review synthesizes current knowledge about arenaviral evolution, ecology, transmission patterns, life cycle, modulation of host immunity, disease pathogenesis, as well as discusses recent development of preventative and therapeutic pursuits against this group of deadly viral pathogens.